2021
DOI: 10.25259/sni_611_2021
|View full text |Cite
|
Sign up to set email alerts
|

Transdural reduction of a bone fragment protruding into the spinal canal during surgical treatment of lumbar burst fracture: A case report

Abstract: Background: There have been many reports on the clinical, radiographic, and surgical management of thoracolumbar burst fractures attributed to high-energy trauma. Interestingly, few reports have described how to extract bone fragments associated with these injuries protruding into the spinal canal contributing to significant neurological deficits. Methods: An 18-year-old male presented with a severe L3-level paraparesis (i.e., loss of motor/sensory function below L3 lower extremity hyporeflexia, and sphinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition to the classic low back pain, it can also cause complications such as progressive spinal deformity, pulmonary dysfunction, severe back pain, deep vein thrombosis, muscle atrophy, pressure ulcers, sleep disturbance, depression, intestinal obstruction and, sometimes is easily overlooked, LSS. Many studies thus far were concerned with the relationship between lumbar burst fractures and LSS 12,26,27 , but few studies have investigated LSS in patients with the LCF, although has a higher morbidity 28 . We speculate that lumbar VCF and burst fractures may have some similarities in the pathogenesis of LSS, such as the deformation of the vertebral body directly compressing the spinal canal 29 or the loss of vertebral body height and the intervertebral foramen leading to lower extremity symptoms 30 .…”
Section: Surgical Options and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the classic low back pain, it can also cause complications such as progressive spinal deformity, pulmonary dysfunction, severe back pain, deep vein thrombosis, muscle atrophy, pressure ulcers, sleep disturbance, depression, intestinal obstruction and, sometimes is easily overlooked, LSS. Many studies thus far were concerned with the relationship between lumbar burst fractures and LSS 12,26,27 , but few studies have investigated LSS in patients with the LCF, although has a higher morbidity 28 . We speculate that lumbar VCF and burst fractures may have some similarities in the pathogenesis of LSS, such as the deformation of the vertebral body directly compressing the spinal canal 29 or the loss of vertebral body height and the intervertebral foramen leading to lower extremity symptoms 30 .…”
Section: Surgical Options and Prognosismentioning
confidence: 99%
“…When both LCF and LSS occur in a patient at the same time, whether there is a correlation between these two diseases is an interesting question. Many current studies have shown that changes in spinal balance in patients with osteoporosis 10 , loss of vertebral height 11 , and direct posterior displacement of the vertebral body after compression fractures 12 can lead to spinal stenosis. On the other hand, one previous study of older women found that 79.2% of LSS patients had osteoporosis or osteopenia 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 3 ] Because burst fractures often involve damage to the column and posterior structures of the spine, the fracture block may invade the spinal canal and compress the spinal cord or the cauda equina, causing corresponding neurological dysfunction. [ 4 ] Because of the difference in the degree of fracture and the degree of completeness of neurological function, there are many controversies in the treatment of thoracolumbar burst fractures. [ 5 , 6 ] In recent years, with the development of posterior pedicle fixation devices, posterior pedicle screw fixation has been widely used clinically and has achieved good clinical results.…”
Section: Introductionmentioning
confidence: 99%